Effects of nodes and finger-jointed bamboo strips on properties of laminated bamboo timber from Gigantochloa scortechinii gamble - Anokye, Rogerson (2015)
Bamboo has good potential as an alternative to wood-based materials especially in wood based composite industry to mitigate against the over increasing decline of the forest resources in Ghana. The abundance of wild bamboo in the Ghana with its numerous potentials of cultivating and developing bamboo necessitated the study into the development of high grade building and furniture material from bamboo as an alternative material and to verify its physical and mechanical properties. Research has shown that, node of bamboo is the weakest point and requires the removal and or rearrangement of the nodes to improve the strength of laminated bamboo timber (LBT) products. Gigantochloa scortechinii and Bambusa vulgaris species from Malaysia were adopted for the study due to the species’ availability and proximity as well as the environmental conditions’ similarities to that of Ghana. The basic physical and mechanical properties of the two species at three different height levels were assessed to determine their similarities. They were also to serve as a guide in the determination of strength properties of the LBT as well as its working qualities and environmental tolerability. The results revealed that, both species have similar basic characteristics in both physical and mechanical properties to indicating G. scortechinii’s appropriateness for the study. The processing of bamboo into strips using split squaring and V-grooving processing methods were compared. This was done in order to recommend the best processing method whilst, the bondability properties of the strips were also assessed in order to proposed the proper method and procedure of bonding, in the lamination process of the LBT. The results of the former confirmed V-grooving method’s superiority in terms of processing recovery. However, split squaring method was selected for the processing of LBT due to its time efficiency of about thrice to that of V-grooving method. Accordingly, basal section of G. scortechinii was then selected for the development of a non-nodal finger-jointed laminated bamboo timber (LBT). The strength performance with respect to finger-jointed, nodal and non-nodal or clear joint types, phenol formaldehyde and polyvinyl acetate glue types, 200 g/m2 and 250 g/m2 glue spread rates and joint intervals of 0, 5, 10 and 15 cm were all examined. The results revealed that, the mechanical properties of non – nodal finger - jointed LBT has higher MOE and MOR than members formed with nodes but slightly lower in strength than clear samples. Though there was a similar failure behaviour within the samples in the same group of nodal and non-nodal finger-jointed, non-nodal finger jointed LBT bonded with 200 g/m2 PF showed a higher performance than PVAc on both MOE and MOR. The flexural performance of the LBT with finger-joints increases with increase in joint intervals. From the results gathered on bending, compression and shear strength on the non-nodal finger-jointed LBT as well as the dimensional stability of it, can be concluded that, the product is extremely satisfactory for interior furniture production. The overall results of the dimensional stability test on the newly developed LBT was found to have mean thickness swelling (TS), water absorption (WA), and linear expansion (LE) (parallel and perpendicular to grain) values within the normal behaviour of bamboo laminated lumber, although the mean moisture absorption (MA) was slightly higher than those obtained by others. Additionally, the results obtained for the LE parallel and perpendicular to grain matches the radial-tangential swelling ratio of 1.0: 1.2 which is more likely to stabilize the LBT when subjected to 55% and 90% relative humidity environmental conditions. Generally, the removal and the replacement of nodes with finger joints respectively has shown a considerable improvement in the strength properties of LBT. However, the strength attained together with the bonding qualities make LBT bonded with PF glue at 200 g/m2 spread rate a strong material with better dimensional stability suitable for interior applications.